The Potential of Deleterious rhizobacteria to Control Primary Weed Echinochloa sp. on Rice - Hoesain, Mohammad; Masnilah, Rachmi; Nurchayanti, Suhartiningsih Dwi; Pradana, Ankardiansyah Pandu; Alfarisy, Fariz Kustiawan; Sari, Dwi Tirta; Ramadhan, Farchan Mushal Al; Rismayani; Tarigan, Sri Ita (Universitas Negeri Semarang, 2024)
Deleterious rhizobacteria (DRB) is one of the rhizobacteria that can be used as a bioherbicide and can stimulate plant growth. The objectives that can be obtained from this study are to determine the potential of DRB on the growth of weeds Echinochloa crusgalli and Echinochloa colona on rice. Variables observed in this study were identification of secondary metabolites, measurement of weed sprouts, percentage effectiveness of bacterial isolates against weed seeds, normal sprouts, abnormal sprouts, fresh seeds that did not grow and dead seeds. The aim of this study is to explore biological agents that can be used to control the main weeds of rice crops. This candidate could be a recommendation for environmentally friendly controls. Exploration of the DRB group was obtained by collecting soil samples around the roots of rice crops. Then isolate it, identify as morphologically and physiologically, and test it in vitro studies. The results showed that DRB had the potential to control weed growth and could stimulate the growth of rice. The application of PFA and PFB isolates had a significant effect on inhibiting the length of weed roots and buds, the average percentage of control effectiveness > 80-90%. Novelty in this study could be found as candidate groups of DRB bacteria with specific locations to control the weed Echinochloa sp. on rice crops. For society, this research could be an alternative to reduce dependence on synthetic herbicides . DRB has the potential to be formulated into a bioherbicide to control weeds.